From toys to tools: The co-evolution of technological and entrepreneurial developments in the drone industry - Giones, Ferran; Brem, Alexander (Business Horizons, 2017)
There is undoubtedly hype around drones and their applications for private and professional users. Based on a brief overview of the development of the drone industry in recent years, this article examines the co-evolution of drone technology and the entrepreneurial activity linked to it. Our results highlight the industry emergence described as concept validation, including product as well as market growth with different phases of technological meaning change. We argue that further steps are needed to develop drones from nice toys to professional tools—from photography and filming applications to inspection services and large cargo logistics. For innovation managers and entrepreneurs, we describe what triggers the emergence of a technology and attracts the needed actors to unleash its transformative potential. Our research is based on industry reports, news, and market studies as well as interviews with four industry actor
Keywords: Technological progress; Entrepreneurial activity; Drones; Drone industry; Emerging industries; Unmanned aircraft systems; Unmanned aerial vehicles; Drone development